2017
DOI: 10.1136/bmjopen-2017-017170
|View full text |Cite
|
Sign up to set email alerts
|

Clinical examination, critical care ultrasonography and outcomes in the critically ill: cohort profile of the Simple Intensive Care Studies-I

Abstract: PurposeIn the Simple Intensive Care Studies-I (SICS-I), we aim to unravel the value of clinical and haemodynamic variables obtained by physical examination and critical care ultrasound (CCUS) that currently guide daily practice in critically ill patients. We intend to (1) measure all available clinical and haemodynamic variables, (2) train novices in obtaining values for advanced variables based on CCUS in the intensive care unit (ICU) and (3) create an infrastructure for a registry with the flexibility of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…All patients were included within the first 24 h of their ICU admission and underwent clinical examination, immediately followed by CCUS. Patients were included by medical research interns and PhD students who had received a focused CCUS training course given by experienced cardiologist-intensivists (protocol in Supplements 1) [16]. These researchers were not involved in patient care, and their findings were not revealed to the patients' caregivers.…”
Section: Design Setting and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were included within the first 24 h of their ICU admission and underwent clinical examination, immediately followed by CCUS. Patients were included by medical research interns and PhD students who had received a focused CCUS training course given by experienced cardiologist-intensivists (protocol in Supplements 1) [16]. These researchers were not involved in patient care, and their findings were not revealed to the patients' caregivers.…”
Section: Design Setting and Patientsmentioning
confidence: 99%
“…Our aim was to study the diagnostic performance of clinical examination in a twostep approach: to establish (1) which combination of clinical examination findings are independently associated with cardiac index and (2) the performance of clinical signs to diagnose a low or high cardiac index. The Simple Intensive Care Studies-I (SICS-I) was designed to assess the ability of clinical examination to estimate cardiac index and to identify patients with a low or high cardiac index [16].…”
Section: Introductionmentioning
confidence: 99%
“…Patient characteristics were registered at admission . All patients underwent clinical examination within 24 hours after ICU admission according to a prespecified protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The SICS‐I was designed to address multiple hypotheses on six different outcomes and, therefore, the acute kidney injury outcome was adjusted for multiple hypothesis testing . We refer to our SAP for more details, but in short, a P ‐value of 0.015 indicated statistical significance and p‐values between 0.015 and 0.05 indicated suggestive significance with an increased family‐wise error rate .…”
Section: Methodsmentioning
confidence: 99%
“…Curiously, Hiemstra et al [4] reported an unexpected similar failure rate in this study that included mostly medical patients. Even more surprising, Hiemstra et al [6] previously mentioned in their preliminary report of the first 704 included patients that echocardiography was judged by experts to be of sufficient quality in 632 patients (90%), a much more usual failure rate. The second interesting finding is that CI was frequently low in this unselected population of ICU patients.…”
mentioning
confidence: 98%